2019
DOI: 10.1002/job.2400
|View full text |Cite
|
Sign up to set email alerts
|

The relentless pursuit of perfectionism: A review of perfectionism in the workplace and an agenda for future research

Abstract: Summary The pursuit of perfectionism resonates with many individuals across workplaces resulting in a recent flurry of research on the topic. Although extant research has examined the costs and benefits of perfectionism at work, these efforts are scattered across multiple disciplines and utilize varying conceptualizations. As a result, we lack a coherent understanding of how perfectionism influences work behavior. To address this issue, we integrate the nascent but fragmented perfectionism at work literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 244 publications
(305 reference statements)
10
79
4
Order By: Relevance
“…This result extended prior evidence on effects of DPC on average levels of work‐related worry and rumination (Flaxman et al, , ) and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett, Hewitt, Blankstein, & Gray, ; Flett, Madorsky, Hewitt, & Heisel, ) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within‐person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, and Ocampo et al, for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between‐persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, , ) results because they found that DPC and DPS were associated with unique forms of cognitive work‐related behavior during evening leisure time (i.e., DPC with work‐related worry/rumination but not positive thinking about work and DPS with positive thinking about work but not work‐related worry/rumination).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result extended prior evidence on effects of DPC on average levels of work‐related worry and rumination (Flaxman et al, , ) and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett, Hewitt, Blankstein, & Gray, ; Flett, Madorsky, Hewitt, & Heisel, ) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within‐person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, and Ocampo et al, for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between‐persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, , ) results because they found that DPC and DPS were associated with unique forms of cognitive work‐related behavior during evening leisure time (i.e., DPC with work‐related worry/rumination but not positive thinking about work and DPS with positive thinking about work but not work‐related worry/rumination).…”
Section: Discussioncontrasting
confidence: 99%
“…More specifically, such less detrimental effects of perfectionistic strivings compared to perfectionistic concerns were also reported for indicators of distress and detachment in the workplace (see Harari, Swider, Steed, & Breidenthal, 2018 (Flaxman et al, 2017(Flaxman et al, , 2012 and on associations between perfectionistic cognitions and negative forms of perseverative thinking (not differentiating between PSC and PCC; Flett, Hewitt, Blankstein, & Gray, 1998;Flett, Madorsky, Hewitt, & Heisel, 2002) to specifically investigating fluctuations in perfectionistic concerns in the form of current thoughts on the within-person level. In contrast to our expectations and to evidence on the role of trait perfectionism in the workplace (see Harari et al, 2018 andOcampo et al, 2019 for recent reviews), that consistently reported detrimental effects of perfectionistic concerns not only on indicators of strain and organizational behavior but also on motivational variables and detachment, we found no evidence that associations between the two dimensions of dispositional perfectionism and psychological detachment were different from zero at the between-persons level. This was surprising given Flaxman and colleagues' (Flaxman et al, 2017(Flaxman et al, , 2012…”
Section: The Mediating Process In the Sd Modelcontrasting
confidence: 99%
“…These results are consistent with prior evidence that has established associations between positive emotionality and self-regulation, and between negative emotionality and a lack of selfregulation [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Results presented in this research study also reveal the specific strategic coping behaviors that are associated with students' emotions and their ultimate emotional state of engagement vs. burnout, suggesting that coping strategies are a meta-emotional variable, or, as their name implies, a behavioral strategy, adjusted or maladjusted, for managing emotions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has reported factors that predict and predispose both constructs [52]. Achievement emotions (positive vs. negative) have been differentially associated with burnout [53], and engagement has been shown to favor metacognitive self-regulation and knowledge construction [54].…”
Section: Engagement-burnout As a Motivational Variable Of The Learninmentioning
confidence: 99%
See 1 more Smart Citation